Development of differential absorption spectroscopy techniques for a sub-millimeter wave radar system - Göbel, Sebastian (My University, 2021)
To reduce the negative impact of the increasing energy demands of society onto the climate, the use of renewable resources is essential. In this context, power plants for combustion of sustainable biomass fuels play an important role. For an efficient combustion process to take place, mixing of the fluid solids, the gas-solid contacts, and heat transfer are of importance, and fluidized bed technology is used for large-scale combustion and gasification of solid fuels. For further optimization of combustion, the mixing processes of fluidized beds are under investigation using experiments and theoretical modelling. However, theoretical methods are often hard to validate with appropriate experimental results, and the experimental methods often lack the desired resolution in time and space. In contrast, a sub-millimeter wave radar may be a suitable tool to resolve particle concentrations and velocities. Furthermore, the existence of water absorption lines within the radars frequency range can facilities even water vapor content extraction. In this thesis, a retrieval method inspired by NASA’s Vapor In-Cloud Profiling Radar (VIPR) project is synthesized and evaluated using simulations to achieve a sense of expectations, and experimentally in a lab environment using falling particles to mimic the fluidized bed. Further, a fixed target method is evaluated which could prove helpful in measuring water vapor. Experimentally, the initial tests show promising performance of range resolved measurements of particle concentration, suggesting further evaluation is of interest.
Keywords: radar; spectroscopy